'Free Anwar' campaign 'a ploy' - Daily Express, (KK) (Daily Express (KK), 2012)
KUALA LUMPUR: The "Free Anwar" Campaign 901, planned by Parti Keadilan Rakyat (PKR) Youth, is seen as merely championing the interests of opposition chief Datuk Seri Anwar Ibrahim.